The diagnostics of a state of an aesthetic development of the elementary' school pupils during the choreographic activity - Yu.V. Honcharenko (Academy of Cognitive and Natural Sciences, 2006)
The article represents the results of diagnostics of the levels of an aesthetic development of pupils ofprimary classes huy resources of choreography.